IgM rheumatoid factor amplifies the inflammatory response of macrophages induced by the rheumatoid arthritis-specific immune complexes containing anticitrullinated protein antibodies. Issue 7 (11th March 2014) - Laurent, Lætitia; Anquetil, Florence; Clavel, Cyril; Ndongo-Thiam, Ndiémé; Offer, Géraldine; Miossec, Pierre; Pasquali, Jean-Louis; Sebbag, Mireille; Serre, Guy
Abstract : Objectives: Anticitrullinated protein antibodies (ACPA) are specifically associated with rheumatoid arthritis (RA) and produced in inflamed synovial membranes where citrullinated fibrin, their antigenic target, is abundant. We showed that immune complexes containing IgG ACPA (ACPA-IC) induce FcγR-mediated tumour necrosis factor (TNF)-α secretion in macrophages. Since IgM rheumatoid factor (RF), an autoantibody directed to the Fc fragment of IgG, is also produced and concentrated in the rheumatoid synovial tissue, we evaluated its influence on macrophage stimulation by ACPA-IC. Methods: With monocyte-derived macrophages from more than 40 healthy individuals and different human IgM cryoglobulins with RF activity, using a previously developed human in vitro model, we evaluated the effect of the incorporation of IgM RF into ACPA-IC. Results: IgM RF induced an important amplification of the TNF-α secretion. This effect was not observed in monocytes and depended on an increase in the number of IgG-engaged FcγR. It extended to the secretion of interleukin (IL)-1β and IL-6, was paralleled by IL-8 secretion and was not associated with overwhelming secretion of IL-10 or IL-1Ra. Moreover, the RF-induced increased proinflammatory bioactivity of the cytokine response to ACPA-IC was confirmed by an enhanced, not entirely TNF-dependent, capacity of the secreted cytokine cocktail to prompt IL-6 secretion by RA synoviocytes. Conclusions: By showing that it can greatly enhance the proinflammatory cytokine response induced in macrophages by the RA-specific ACPA-IC, these results highlight a previously undescribed, FcγR-dependent strong proinflammatory potential of IgM RF. They clarify the pathophysiological link between the presence of ACPA and IgM RF, and RA severity.